Content Strategies in the Digital Era: A Qualitative Analysis of Audience Responses to Flexing and Educational Content (International Forum of Researchers and Lecturers, 2025)
This study investigates audience engagement with two dominant types of digital content on social media platforms Instagram and TikTok: flexing content, which includes hedonistic and performative self-presentation, and educational content, which emphasizes informative and value-based narratives. Although both content types are widely consumed, their comparative effects on user behavior, cognition, and emotional response have not been sufficiently examined. This research addresses a critical gap in the digital attention economy, where engagement is often measured by shallow metrics such as likes and views, rather than by meaningful interaction or long-term impact. Employing a qualitative-comparative approach, the study combines thematic analysis of engagement metrics from six influencer accounts with in-depth interviews involving twelve social media users aged 18–30 in Indonesia. The findings reveal a clear distinction in how audiences respond to these content types. Flexing content tends to attract high visibility through likes and views but often leads to emotional fatigue, feelings of inadequacy, and eventual disengagement. On the other hand, educational content encourages deeper cognitive and emotional engagement, with higher rates of comments, shares, and saves, and is often associated with authenticity and perceived personal value. These results align with theories of impression management and social comparison, showing how different content types fulfill distinct psychological and symbolic functions for users. Based on the data, the study proposes a conceptual model to differentiate between surface-level and substantial digital engagement. The conclusion emphasizes that while flexing may offer short-term visibility, it is the relevance, usefulness, and authenticity of educational content that sustain long-term audience connection. These insights offer strategic guidance for content creators, educators, and digital marketers seeking to foster more meaningful relationships with their audiences in an increasingly saturated and competitive platform-driven environment.